The Caryophyllaceae family in the state of Aguascalientes, Mexico - Sandoval-Ortega, Manuel Higinio; Siqueiros-Delgado, María Elena; Cerros-Tlatilpa, Rosa; Ocampo, Gilberto (Instituto de Ecología, A.C., 2019)
Background and Aims: The Caryophyllaceae family has a wide geographical distribution, especially in temperate and warm regions of the northern hemisphere. Its species mainly inhabit open environments or disturbed sites. The aim of the present study was to carry out the inventory, document the distribution and perform the taxonomic treatment of the Caryophyllaceae species present in the state of Aguascalientes, Mexico.Methods: Collections were made throughout the state from August 2012 to June 2015. In each collection site geographic coordinates were taken based on Datum WGS 84 and the type of vegetation was recorded. The collected material was identified by means of specialized taxonomic keys and compared with herbarium material. For the taxonomic treatment descriptions were made for family, genera and species, as well as dichotomous keys for their identification. Distribution maps were prepared based on the data collected in the field and the herbarium specimens consulted.Key results: In Aguascalientes, the Caryophyllaceae family is represented by 11 genera and 21 species, of which four are new records for the state. The greatest number of species is found in temperate climate vegetation types, mainly Quercus forest and mixed forest, followed by xerophilous scrubland and grassland. The municipality in which the greatest number of species is distributed is San José de Gracia, followed by Calvillo. Of the total number of species found in state five are endemic to Mexico.Conclusions: The richness of genera and species of the Caryophyllaceae family present in Aguascalientes is comparable with larger states. The present work extends the knowledge of the flora of the state and of the Caryophyllaceae family in Mexico.